Analysis of the Economic Potential of Organic Fertilizer from Biogas Digister Waste (Slurry) - Hamri; Kamil, Kusno; Altim, Muh. Zainal (MultiTech Publisher, 2024)
Fertilization is one of the important activities in cultivation to increase plant productivity. The application of fertilizers into the soil aims to increase and / or maintain soil inorganic fertility, where soil inorganic fertility is assessed based on the availability of nutrients in the soil, both macro nutrients and micro nutrients in biological waste that is easily obtained from the environment around us, recycled and overhauled with the help of decomposer microorganisms such as bacteria and fungi into nutrients that can be absorbed by plants, the decomposition of organic matter into organic fertilizer can take place naturally. The decline in soil organic matter content is thought to be caused by agricultural cultivation methods that pay less attention to organic matter content. One of them is the use of chemical fertilizers that are very intensive. Farmers pay more attention to the addition of chemical nutrients and do not pay attention to organic matter. Organic fertilizers play a role in increasing the physical, chemical and biological fertility of soil and making the use of inorganic fertilizers more efficient. The purpose of this research is to analyze the results of organic liquid fertilizer produced by the biogas digester (slurry), calculate the economic potential generated from the biogas digester. The capacity of the alt digester used is four cubic, with a mixture of one liter of cow dung, four liters of water, how to fill it every day until the eighteenth day produces nitrogen which is still low, which is an average average of 0.072%, for phosphorus 5.13 mg/100g and potassium is 4.87 mg/100 grams. As for the potential income of Rp 159.500,- for 10 days with an input of one liter of cow dung with four liters of water, if one month is assumed to be 30 days then 3 x Rp 159.500,- = Rp 478 500,- per month. However, if the input capacity is increased to ten times, the potential income is IDR 4,785,000 per month.